2021
DOI: 10.1038/s10038-020-00888-5
|View full text |Cite
|
Sign up to set email alerts
|

Independent and cumulative coeliac disease-susceptibility loci are associated with distinct disease phenotypes

Abstract: The phenotype of coeliac disease varies considerably for incompletely understood reasons. We investigated whether established coeliac disease susceptibility variants (SNPs) are individually or cumulatively associated with distinct phenotypes. We also tested whether a polygenic risk score (PRS) based on genome-wide associated (GWA) data could explain the phenotypic variation. The phenotypic association of 39 non-HLA coeliac disease SNPs was tested in 625 thoroughly phenotyped coeliac disease patients and 1817 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 42 publications
1
5
0
Order By: Relevance
“…Moreover, a more recent paper was able, integrating genomic and transcriptomic data, to prioritize genes involved in CeD, and to identify TRAF-type zinc finger domain containing 1 (TRAFD1) as a master regulator of genes involved in interferon (IFN)γ signaling and MHC I antigen processing/presentation[ 8 ]. The different combination of these SNPs could also be associated with a different phenotype, as recently reported by Cerquieira et al [ 9 ], who identified the TLR7/ TLR8 Locus associated with disease onset before 7 years of age, whereas SH2B3/ATXN2, ITGA4/UBE2E3 and IL2/IL21 Loci were associated with later development of CeD and a more severe small bowel mucosal damage. In addition, SH2B3/ATXN2 was associated with type 1 diabetes; in fact some of the identified SNPs are described as predisposing factors also for other autoimmune disorders like type 1 diabetes and Crohn’s disease[ 7 , 10 ], almost suggesting the presence of a common genetic background predisposing to autoimmunity.…”
Section: Introductionsupporting
confidence: 53%
“…Moreover, a more recent paper was able, integrating genomic and transcriptomic data, to prioritize genes involved in CeD, and to identify TRAF-type zinc finger domain containing 1 (TRAFD1) as a master regulator of genes involved in interferon (IFN)γ signaling and MHC I antigen processing/presentation[ 8 ]. The different combination of these SNPs could also be associated with a different phenotype, as recently reported by Cerquieira et al [ 9 ], who identified the TLR7/ TLR8 Locus associated with disease onset before 7 years of age, whereas SH2B3/ATXN2, ITGA4/UBE2E3 and IL2/IL21 Loci were associated with later development of CeD and a more severe small bowel mucosal damage. In addition, SH2B3/ATXN2 was associated with type 1 diabetes; in fact some of the identified SNPs are described as predisposing factors also for other autoimmune disorders like type 1 diabetes and Crohn’s disease[ 7 , 10 ], almost suggesting the presence of a common genetic background predisposing to autoimmunity.…”
Section: Introductionsupporting
confidence: 53%
“…We have previously reported associations of SNPs outside the CCR9 and CCL25 genomic regions with the same phenotypes that were resistant to correction for multiple comparisons. One of these was the association of rs13010713 in integrin subunit alpha 4 gene ( ITGA4 ) with the presence of gastrointestinal symptoms, total or subtotal villous atrophy, and intermediate HLA risk [ 19 ]. ITGA4 codes for the α 4 subunit of heterodimeric integrin molecules involved in adhesion and the pairing of α4 subunit with β 7 subunit promotes homing of T cells to intestinal sites [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…As SNPs identified by sequencing were not available in the Illumina 610-Quad BeadChip array, and thus not genotyped, those having MAF ≥5% were selected to be phased and imputed using a Finnish population-specific panel of 3775 high-coverage (25–30 ×) whole-genome sequences (SISu v3). Sample-wise, variant-wise, and post-imputation QC was applied as previously described [ 19 ]. Phasing of genotyped data was performed with Eagle 2.3.5 ( https://data.broadinstitute.org/alkesgroup/Eagle/ ) and imputation was carried out with Beagle 4.1 (version 08Jun17.d8b, https://faculty.washington.edu/browning/beagle/b4_1.html ) as described in the following protocol: dx.doi.org/10.17504/protocols.io.nmndc5e.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Single nucleotide polymorphisms (SNPs) analysis showed that some loci are associated with more than one CD gene, raising the number of polymorphisms to 57 [ 17 , 18 ]. Cerquieira et al identified the TLR7/TLR8 locus associated with CD onset before seven years of age, whereas the SH2B3/ATXN2, ITGA4/UBE2E3, and IL2/IL21 loci were associated with later development of CD and a more severe mucosal injury [ 19 ]. It seems that their role is to regulate gene expressions via chromatin status, resulting in epigenetic modifications, a new field that is under evaluation [ 20 , 21 ].…”
Section: Genetics and Genes In CDmentioning
confidence: 99%